2022
DOI: 10.3390/ijms231810319
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthroindolizidine Alkaloids Isolated from Tylophora ovata as Potent Inhibitors of Inflammation, Spheroid Growth, and Invasion of Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC), representing the most aggressive form of breast cancer with currently no targeted therapy available, is characterized by an inflammatory and hypoxic tumor microenvironment. To date, a broad spectrum of anti-tumor activities has been reported for phenanthroindolizidine alkaloids (PAs), however, their mode of action in TNBC remains elusive. Thus, we investigated six naturally occurring PAs extracted from the plant Tylophora ovata: O-methyltylophorinidine (1) and its five der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The medicinal properties of the species are often associated with the phenanthroindolizidine alkaloids (PIA) found in plants of the genus Vincetoxicum as well as in other genera. In vitro studies found potent anti-inflammatory activities in RAW264.7 mouse macrophage cell line for different PIAs (Yang et al, 2006; Chou et al, 2017; Reimche et al, 2022). However, PIAs are also known to be strongly cytotoxic and have therefore also been explored in terms of their anticancer properties.…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal properties of the species are often associated with the phenanthroindolizidine alkaloids (PIA) found in plants of the genus Vincetoxicum as well as in other genera. In vitro studies found potent anti-inflammatory activities in RAW264.7 mouse macrophage cell line for different PIAs (Yang et al, 2006; Chou et al, 2017; Reimche et al, 2022). However, PIAs are also known to be strongly cytotoxic and have therefore also been explored in terms of their anticancer properties.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, as one of the typical features of TNBC, refers to the condition in which oxygen is insufficient to support the body’s metabolism [ 12 , 13 ]. The hypoxia condition occurs when the vascular supply is interrupted or tumor growth exceeds its vascular supply [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, as one of the typical features of TNBC, refers to the condition in which oxygen is insu cient to support the body's metabolism [12,13]. The hypoxia condition occurs when the vascular supply is interrupted or tumor growth exceeds its vascular supply [14,15].…”
Section: Introductionmentioning
confidence: 99%